Cerebellar Theta Burst Stimulation on Walking Function in Stroke Patients: A Randomized Clinical Trial - Xie, Yun-Juan; Wei, Qing-Chuan; Chen, Yi; Liao, Ling-Yi; Li, Bao-Jin; Tan, Hui-Xin; Jiang, Han-Hong; Guo, Qi-Fan; Gao, Qiang (Frontiers in Neuroscience, 2021)
Objectives: The objective of this study was to explore the efficacy of cerebellar intermittent theta burst stimulation (iTBS) on the walking function of stroke patients. Methods: Stroke patients with walking dysfunction aged 25–80 years who had suffered their first unilateral stroke were included. A total of 36 patients [mean (SD) age, 53 (7.93) years; 10 women (28%)] were enrolled in the study. All participants received the same conventional physical therapy, including transfer, balance, and ambulation training, during admission for 50 min per day during 2 weeks (10 sessions). Every session was preceded by 3 min procedure of cerebellar iTBS applyed over the contralesional cerebellum in the intervention group or by a similar sham iTBS in control group. The groups were formed randomly and the baseline characteristics showed no significant difference. The primary outcome measure was Fugl–Meyer Assessment–Lower Extremity scores. Secondary outcomes included walking performance and corticospinal excitability. Measures were performed before the intervention beginning (T0), after the first (T1) and the second (T2) weeks. Results: The Fugl–Meyer Assessment for lower extremity scores slightly improved with time in both groups with no significant difference between the groups and over the time. The walking performance significantly improved with time and between group. Two-way mixed measures ANOVA showed that there was significant interaction between time and group in comfortable walking time (F2,68 = 6.5242, P = 0.0080, η2partial = 0.276, ε = 0.641), between-group comparisons revealed significant differences at T1 (P = 0.0072) and T2 (P = 0.0133). The statistical analysis of maximum walking time showed that there was significant interaction between time and groups (F2,68 = 5.4354, P = 0.0115, η2partial = 0.198, ε = 0.734). Compared with T0, the differences of maximum walking time between the two groups at T1 (P = 0.0227) and T2 (P = 0.0127) were statistically significant. However, both the Timed up and go test and functional ambulation category scale did not yield significant differences between groups (P > 0.05). Conclusion: Our results revealed that applying iTBS over the contralesional cerebellum paired with physical therapy could improve walking performance in patients after stroke, implying that cerebellar iTBS intervention may be a noninvasive strategy to promote walking function in these patients. This study was registered at ChiCTR, number ChiCTR1900026450.